La mobilità intelligente: miglioramento del well-being e salvaguardia dell’ecosistema (European journal of volunteering and community-based projects, 2024)
Purpose: The article aims to investigate the actors who generate ecosystem value, the stakeholders who capture it, the concept of value generated/captured, focusing on the field of Smart Mobility (SM). This sector represents a critical context for analyzing possible innovative landscapes in terms of sustainability. The paper studies SM in the Italian city of Venice, the world capital of sustainability.Methodology: The article uses a qualitative methodology based on multiple case studies by interviewing the chiefs of five startup companies from the Venetian, ecosystem involved in the SM field.Results: Findings confirm what is present in the literature, broadening the field of analysis and suggesting proactive actions. SM increases mobility, offers flexibility, and guarantees greater capillarity and service personalization. At the same time, it allows a reduction in costs for both operators and users, becoming both an economically interesting activity to carry out for entrepreneurs and a positive panorama for Local Authorities, which can provide the necessary service to the resident and non-resident population without the need to provide excessive subsidized contributions. There is an improvement in the quality of life in general and specifically in the user's travel experience. The positive impact on the environment is also indisputable. In fact, there has been a decrease in energy consumption, fuel consumption, and polluting emissions. However, there are some obstacles that have not yet been overcome.Originality: While there are studies on value creation from an ecosystem point of view in the literature, the dynamics of ecosystem value creation in the SM sector are still a puzzle. This underscores the need for in-depth investigations to fully understand and harness the potential of this sector.
Keywords: smart mobility; quality of life; sustainability; business ecosystems